STRATEGI PROMOSI MELALUI ADVOKASI DAN PEMBERDAYAAN KELUARGA TERHADAP PEMBERIAN MAKANAN BERGIZI BALITA 0-23 BULAN DI WILAYAH PUSKESMAS ALAK NUSA TENGGARA TIMUR - Frans Salesman (CHMK NURSING SCIENTIFIC JOURNAL, 2017)
Introduction. Intake of nutritional and nutritional foods is the key to growth of infants. But for mothers with low education do not understand the importance of providing nutritious food for their infants aged 0-23 months. Purpose. Analyze the effectiveness of health promotion through advocacy and training of mothers in Alak Community Health Center. Methods. The study used analytical survey with cross sectional approach. Mother Research Population with 0-23 month old baby counted 257 people. Sampling technique sampling purposed 132 respondents. Data analysis technique using Chi Square and Odd Ratio. Results. Advocacy mothers have  tendency to manage nutritious food 7.90 times compared  mothers who are not advocated with Relative Risk 2.14, meaning that advocates have 2.14 times more chance managing nutritious food than mothers who do not get advocacy. While the mothers who received training have  tendency 10 times greater applying nutritious food processing than mothers who are not trained, with Relative Risk 2.05. This means the opportunity to manage nutritious food 2.05 times greater than mothers who are not trained. Conclusion. Advocacy and empowerment in the form training is  health promotion strategy to increase knowledge and skills of mothers about the management of nutritious food to support the growth of infants aged 0-23 months.Keyword. Advocacy strategies, empowerment, healthy babies